Re-positive Cases of Nucleic Acid Tests in Discharged Patients With COVID-19: A Follow-Up Study - Qiao, Xi-Min; Xu, Xiao-Feng; Zi, Hao; Liu, Guo-Xiong; Li, Bing-Hui; Du, Xiang; Tian, Zhi-Hai; Liu, Xiao-Ying; Luo, Li-Sha; Wang, Xiao (Frontiers in Medicine, 2020)
Background: The frequent emergence of the re-positive patients with COVID-19 has been a potential threaten worldwide. This study aimed to describe data from admission to follow-up for patients with COVID-19, and analyze the possible causes for re-positive nucleic acid test, to provide more scientific basis for reducing the numbers of re-positive patients after discharge. Methods: We retrospectively recorded 15 patients with COVID-19 admitted to the Central Hospital of Xianyang, China. The baseline, exposure histories, clinical syndromes, laboratory characteristics, nucleic acid and follow-up tests were analyzed, and the radiological characteristics of re-positive patient at different periods were compared. Results: 8 (53.33%) patients had the history of travel to Wuhan, 4 (26.67%) patients had close contact with confirmed patients, and 1 (6.67%) patient had close contact with suspected patients. After treatment, all patients had two consecutively negative nucleic acid and were discharged from hospital. All patients were followed-up for more than 14 days, and the average time from discharge to the first follow-up was 14.67±3.31 days (from 9 to 22 days). Most patients showed no clinical symptom and negative nucleic acid, while one patient felt itchy throat and her CT scan showed a light density shadow in the right lower lobe of the lung, and the nucleic acid turned positive again. The second follow-up of the other 14 patients (except the re-positive one) was conducted 20.80±7.78 days (from 13 to 30 days) after discharge, and all of them had negative nucleic acid. The positive patient was immediately readmitted and received a new round of treatment. Her family members and colleagues remained healthy until now. Conclusions: The quality of nucleic acid testing reagents should be enhanced, and the training of nucleic acid sampling operators should be strengthened to reduce the false-negative results in the nucleic acid of SARS-CoV-2; the clinical specimens of throat and nasopharynx swabs can be collected at the same time; IgM- and IgG-specific antibodies of SARS-CoV-2 should be carried out for discharged patients; the radiological characteristics should be evaluated strictly; the discharge standard can be specified according to the baseline, severity of disease of patients.